Negative electrode material for sodium ion battery, preparation method of negative electrode material, negative electrode plate and sodium ion battery

By using gasified ash slag to prepare sodium ion battery negative electrode materials, the problems of high cost and insufficient performance of existing materials are solved, low-cost and high-efficiency sodium ion battery negative electrode materials are realized, and the industrial application of sodium ion batteries is promoted.

CN119706783AActive Publication Date: 2025-03-28CHINA PETROLEUM & CHEMICAL CORP +1
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202311285355.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-09-28
Publication Date
2025-03-28
Estimated Expiration
2043-09-28

AI Technical Summary

Technical Problem

The high cost of the negative electrode materials of existing sodium ion batteries, low efficiency for the first time, and insufficient circulation and rate performance, limiting the industrial application of sodium ion batteries.

Method used

The gasified ash slag is used as raw material to prepare the negative electrode material of sodium ion battery through ball milling, surface acid removal, wet ball milling and spray drying, and finally calcination is carried out to improve the performance of the material.

Benefits of technology

The prepared negative electrode material has low cost, high efficiency for the first time, and good circulation performance. It is suitable for a variety of application scenarios of sodium ion batteries, and uses gasified ash slag to achieve high value-added resource utilization.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119706783A_ABST
    Figure CN119706783A_ABST
Patent Text Reader

Abstract

The invention relates to a negative electrode material for a sodium ion battery, a preparation method of the negative electrode material, a negative electrode plate and the sodium ion battery. The preparation method comprises the following steps that S1, gasification ash is subjected to first ball milling treatment, a first product is obtained, and the gasification ash comprises ash generated in the heavy oil gasification process; s2, carrying out surface deacidification treatment on the first product to obtain a second product; s3, carrying out second wet ball milling treatment and spray drying treatment on the second product to obtain a third product; and S4, carrying out roasting treatment on the third product. The sodium-ion battery negative electrode material is prepared by taking the gasified ash as the raw material, so that the cost is low, the ash is utilized at a high added value, and the application prospect is wide.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present disclosure relates to the technical field of sodium ion batteries, and in particular, to a negative electrode material for a sodium ion battery and a preparation method thereof, a negative electrode sheet and a sodium ion battery. Background Art

[0002] Sodium has abundant reserves, wide distribution and low price, which has made sodium-ion batteries a hot topic in the field of electrochemical energy storage. Currently, sodium-ion batteries have been applied in fields such as low-speed electric vehicles and large-scale energy storage, and the market is gradually opening up. It is foreseeable that sodium-ion batteries will become an important supplement to lithium-ion battery technology, and the two will show a relationship of common development and complementary application fields.

[0003] There are many types of negative electrode materials for sodium-ion batteries, among which carbon-based materials have become the best negative electrode materials at present due to their high performance and wide material sources. Hard carbon is considered to be the most ideal carbon-based sodium storage material due to its excellent sodium storage capacity. However, the disadvantages of hard carbon negative electrode are low first coulombic efficiency, high carbonization cost, insufficient cycle performance and rate performance. Unlike hard carbon, although soft carbon has low specific capacity, it has high first coulombic efficiency, low manufacturing cost, and easy process control. It is a sodium-ion battery negative electrode material with great potential.

[0004] CN115084436A discloses the preparation and application of a pitch-based soft carbon negative electrode material for sodium ion batteries. Under inert gas, asphalts with different softening points are matched and calcined at low temperature to obtain soft carbon. CN111293309A discloses a method for improving the performance of coal-based sodium ion battery negative electrode materials and its application. The coal-based material is mixed with a soft carbon precursor, and after low-temperature treatment, it is placed in a high-temperature carbonization furnace for carbonization to obtain an amorphous carbon material, which is the coal-based sodium ion battery negative electrode material. CN113526489A discloses a method for improving the performance of a carbon-based negative electrode material for sodium ion batteries and its application. The soft carbon precursor is pre-oxidized and then mixed with a hard carbon precursor to form a mixed material, which is placed in a high-temperature carbonization furnace to obtain an amorphous carbon material, which is the carbon-based negative electrode material for sodium ion batteries. CN114516627A discloses a method for preparing a soft and hard carbon composite nanomaterial, which uses purified weathered coal humic acid as a hard carbon source and asphalt as a soft carbon source, combined with a pore-adjusting agent, to prepare a soft and hard carbon composite sodium ion battery negative electrode material through a two-step high-temperature reaction.

[0005] The soft carbons mentioned in the above literature are one or more of asphalt, petroleum coke, and needle coke, which are the terminal products of petroleum refining. When used as the negative electrode raw material of sodium ion batteries, a certain cost is required. In order to improve the "hardness" of soft carbon materials, the strategy of carbonizing soft and hard carbon precursors together can be adopted to prepare sodium ion battery negative electrode materials, but this undoubtedly increases the cost. In summary, the development of low-cost and easy-to-use sodium ion battery negative electrode materials is of great significance to promoting the industrialization of sodium ion batteries. Summary of the invention

[0006] The purpose of the present disclosure is to provide a negative electrode material for a sodium ion battery and a preparation method thereof, a negative electrode plate and a sodium ion battery. The gasified ash is used as a raw material to prepare the negative electrode material for the sodium ion battery, which not only has low cost but also enables the ash to be used with high added value, and has broad application prospects.

[0007] In order to achieve the above object, the present disclosure provides a method for preparing a negative electrode material for a sodium ion battery in a first aspect, comprising the following steps:

[0008] S1, subjecting gasified ash to a first ball milling process to obtain a first product, wherein the gasified ash includes ash produced during the heavy oil gasification process;

[0009] S2, performing a surface deacidification treatment on the first product to obtain a second product;

[0010] S3, subjecting the second product to a second wet ball milling process and a spray drying process to obtain a third product;

[0011] S4, calcining the third product.

[0012] Optionally, the gasified ash is prepared by removing metal from ash raw materials;

[0013] Preferably, the metal removal process is a hydrometallurgical metal recovery process; optionally, the conditions of the hydrometallurgical metal recovery process include:

[0014] The ash raw material is dried and dehydrated, and then crushed to a particle size of 10 to 100 μm to obtain a crushed ash raw material; the crushed ash raw material is mixed with an acid solution, and then acid hydrolyzed under stirring and reflux; the product obtained by the acid hydrolysis is filtered to obtain gasified ash from which metals have been removed;

[0015] Optionally, the acid solution is selected from one or more of hydrochloric acid, sulfuric acid and nitric acid, preferably sulfuric acid and / or hydrochloric acid; the mixing weight ratio of the acid solution to the crushed ash raw material is 1 to 20:1, preferably 2 to 10:1; Optionally, the stirring reflux temperature is room temperature or 45 to 100°C, and the acid hydrolysis treatment time is 3 to 6 hours;

[0016] Optionally, the ash raw material is selected from one or more of vacuum residue gasification ash, residue hydrocracking tail oil gasification ash, deoiled asphalt gasification ash, catalytic oil slurry ash and ethylene tar ash;

[0017] Optionally, based on the total weight of the ash raw material, the C content in the ash raw material is 82-92 weight%, the H content is 1-10 weight%, the S content is 0.1-5 weight%, the N content is 0.1-5 weight%, the O content is 0.1-5 weight%, and the total content of impurity metals is 0.1-5 weight%, and the impurity metals include Ni, Mo, V, Fe, Na and Ga;

[0018] Preferably, based on the total weight of the gasified ash obtained after metal removal treatment, the C content in the gasified ash obtained after metal removal treatment is 84-92 weight%, the H content is 1-6 weight%, the S content is 0.1-5 weight%, the N content is 0.1-3 weight%, the O content is 0.1-5 weight%, and the total content of impurity metals is 0.1-3 weight%.

[0019] Optionally, the first ball milling treatment conditions include dry ball milling treatment and / or first wet ball milling treatment; preferably, the first wet ball milling treatment;

[0020] Optionally, the conditions of the first wet ball milling treatment include: a ball milling speed of 200 to 1000 rpm, preferably 300 to 800 rpm; a ball milling time of 0.5 to 12 h, preferably 2 to 6 h; a ball milling temperature of 10 to 50° C., preferably 20 to 40° C.; a ball-to-material ratio of 1 to 40, preferably 10 to 30; relative to 1 g of the gasified ash, the amount of the first ball milling solvent is 10 to 200 mL, preferably 20 to 100 mL; optionally, the first ball milling solvent is selected from one or more of ethanol, nitrogen methyl pyrrolidone, cyclohexane, cyclopentane sulfone and tetrahydrofuran;

[0021] Preferably, the method further comprises: drying the product obtained by wet ball milling by rotary evaporation; preferably, the conditions of the rotary evaporation include: a temperature of 40 to 200° C., preferably 40 to 120° C.;

[0022] Optionally, the conditions for the dry ball milling treatment include: a ball milling speed of 200 to 450 rpm, preferably 250 to 350 rpm; a ball milling time of 1 to 8 hours, preferably 2 to 6 hours; a ball milling temperature of 10 to 50° C., preferably 20 to 40° C.; and a ball-to-material ratio of 1 to 40, preferably 10 to 30.

[0023] Optionally, in step S2, the surface acid removal treatment is a water washing treatment or an alkali washing treatment; the water washing treatment and the alkali washing treatment are independently carried out by stirring washing or ultrasonic washing;

[0024] Optionally, the conditions of the water washing treatment include: contacting the first product with deionized water, and then stirring and filtering to obtain a filter residue; repeating the process for more than 3 times to obtain a second product; Optionally, the weight ratio of deionized water to the first product is 1 to 50:1, preferably 10 to 20:1; the conditions of the stirring treatment include: a stirring speed of 100 to 1000 rpm, a stirring time of 2 to 12 h, preferably, a stirring speed of 200 to 400 rpm, and a stirring time of 4 to 8 h;

[0025] Optionally, the conditions of the alkali washing treatment include: the concentration of the alkali solution is 0.1 to 10 mol / L, preferably 0.1 to 5 mol / L; preferably, the alkali solution is selected from an aqueous solution of an alkali; the alkali is selected from one or more of sodium hydroxide, potassium hydroxide, sodium bicarbonate and sodium carbonate; relative to 1 g of the first product, the amount of the alkali solution is 1 to 100 mL, preferably 10 to 50 mL;

[0026] Optionally, when stirring cleaning is adopted, the stirring temperature is 20-60°C, the stirring speed is 200-600rpm, and the stirring time is 1-12h; preferably, the stirring temperature is 20-40°C, the stirring speed is 200-450rpm, and the stirring time is 2-8h;

[0027] Optionally, when ultrasonic cleaning is adopted, the ultrasound is carried out in a closed constant temperature environment, the ultrasound time is 3 to 8 hours, the ultrasound power is 600 to 3000 W, and the ultrasound frequency is 20 to 80 KHz; preferably, the ultrasound time is 3 to 7 hours, the ultrasound power is 400 to 1000 W, and the ultrasound frequency is 40 to 60 KHz.

[0028] Optionally, in step S3, the conditions of the second wet ball milling process include:

[0029] The ball milling speed is 200-1000 rpm, preferably 600-900 rpm; the ball milling time is 1-12 h, preferably 6-12 h; the ball milling temperature is 10-50° C., preferably 20-40° C.; the ball-to-material ratio is 1-40, preferably 15-30; relative to 1 g of the second product, the amount of the second ball milling solvent is 10-100 mL, preferably 20-100 mL; optionally, the second ball milling solvent is selected from one or more of ethanol, nitrogen methyl pyrrolidone, cyclohexane, cyclopentane and tetrahydrofuran;

[0030] Preferably, in step S3, the conditions of the spray drying treatment include: a feed temperature of 120 to 200°C, an outlet temperature of 80 to 100°C, a carrier gas flow rate of 12 to 20 L / min, an inlet pressure of 0.3 to 0.8 MPa, and the carrier gas is selected from one or more of nitrogen and argon;

[0031] Preferably, the feed temperature is 140-190° C., the outlet temperature is 90-100° C., the carrier gas flow rate is 14-18 L / min, and the inlet pressure is 0.4-0.6 MPa.

[0032] Optionally, during the second wet ball milling process, a coating modifier is also added to coat and modify the gasification ash;

[0033] Preferably, the coating modifier is selected from one or more of phenolic resin, epoxy resin, polyfurfuryl alcohol resin and polyethylene;

[0034] Preferably, the weight ratio of the coating modifier to the second product is 0.02 to 0.2:1, preferably 0.05 to 0.15:1.

[0035] Optionally, in step S4, the conditions for the calcination treatment include: heating to 600-1500° C., preferably 750-1300° C., in an inert gas atmosphere, for 1-6 hours, preferably 2-4 hours; optionally, the heating rate is 0.5-5° C. / min, preferably 1-3° C. / min; or,

[0036] The conditions of the calcination treatment include: in an inert gas atmosphere, first heating to 700-1000°C at a first heating rate, keeping warm for 1-6 hours, then heating to 1000-1700°C at a second heating rate, keeping warm for 1-6 hours; preferably, first heating to 800-1000°C at a first heating rate, keeping warm for 2-4 hours, then heating to 1000-1300°C at a second heating rate, keeping warm for 2-4 hours; further preferably, the first heating rate is 1-10°C / min, preferably 1-5°C / min, and the second heating rate is 1-7°C / min, preferably 1-3°C / min;

[0037] Optionally, the inert gas is selected from one or more of nitrogen, helium and argon; the water content of the inert gas is less than 0.1 wt%, and the oxygen content is less than 0.1 wt%.

[0038] A second aspect of the present disclosure provides a negative electrode material for a sodium ion battery prepared according to the method described in the first aspect of the present disclosure.

[0039] Optionally, based on the total weight of the negative electrode material, the carbon content is greater than 90 weight %, the hydrogen content is less than 3 weight %, and the content of other impurity elements is less than 7 weight %, wherein the other impurity elements include one or more of sulfur, nitrogen, oxygen and impurity metals, and the impurity metals include Ni, Mo, V, Fe, Na and Ga;

[0040] Optionally, the negative electrode material D 50 The particle size is 1-50 μm, and the BET specific surface area is 1-500 m 2 / g; preferably, the average particle size of the negative electrode material is 5 to 12 μm, and the BET specific surface area is 1 to 200 m 2 / g.

[0041] A third aspect of the present disclosure provides a negative electrode plate for a sodium ion battery, comprising the negative electrode material described in the second aspect of the present disclosure.

[0042] Optionally, the negative electrode sheet is prepared by a method comprising the following steps: preparing the negative electrode material into a negative electrode slurry, coating the slurry on the surface of a negative electrode current collector, and drying the slurry;

[0043] Preferably, the negative electrode slurry comprises the negative electrode material, a conductive material, a dispersant and a binder;

[0044] Preferably, the weight ratio of the negative electrode material: conductive material: dispersant: binder is 60-96: 0.01-5: 1-10: 1-10, preferably 80-96: 0.02-10: 1-5: 1-5;

[0045] Optionally, the conductive agent material is selected from one or more of highly conductive carbon black, conductive graphite, acetylene black, Ketjen black, single-walled carbon nanotubes, multi-walled carbon nanotubes and carbon nanofibers;

[0046] Optionally, the dispersant is selected from one or more of carboxymethyl cellulose, sodium carboxymethyl cellulose, hydroxyethyl cellulose, sodium alginate, polyvinyl alcohol, chitosan and β-cyclodextrin;

[0047] Optionally, the binder is selected from one or more of styrene butadiene copolymer, polyacrylic acid, sodium polyacrylate, polyimide, polyvinylidene fluoride, nitrile rubber, butadiene rubber, xanthan gum and gum arabic.

[0048] A fourth aspect of the present disclosure provides a sodium ion battery, which includes a positive electrode plate, the negative electrode plate described in the third aspect of the present disclosure, a battery separator and an electrolyte.

[0049] Optionally, the electrolyte is selected from one or more of an ester electrolyte, an ether electrolyte and a sulfone electrolyte;

[0050] Optionally, the ester electrolyte is selected from one or more of ethylene carbonate, vinylene carbonate, vinyl ethylene carbonate, propylene carbonate, ethyl methyl carbonate, dimethyl carbonate, diethyl carbonate and fluorocarbonate;

[0051] Optionally, the ether electrolyte is selected from one or more of 1,3-dioxolane, 1,4-dioxolane, tetrahydrofuran, 2-methyltetrahydrofuran, 1,4-dioxolane, ethylene glycol dimethyl ether, diethylene glycol dimethyl ether, 1H,1H,5H-octafluoropentyl-1,1,2,2-tetrafluoroethyl ether, perfluorohexane, 1,2-bis(cyanoethoxy)ethane and 1,1,2,2-tetrafluoroethyl-2,2,3,3-tetrafluoropropyl ether;

[0052] Optionally, the sulfone electrolyte is selected from one or more of dimethyl sulfoxide, tetramethylene sulfone, ethyl methyl sulfone, tetramethyl sulfone, cyclopentane and methoxyethyl methyl sulfone.

[0053] Through the above technical scheme, the present disclosure provides a negative electrode material for sodium ion batteries and a preparation method thereof, a negative electrode plate and a sodium ion battery. The negative electrode material of the sodium ion battery has low cost, easy raw materials, high first coulomb efficiency, good cycle performance and good safety performance. In addition, the negative electrode material is derived from gasified ash, which can expand the high added value utilization of gasified ash. Compared with the direct incineration of gasified ash, the utilization process is more green and environmentally friendly. The sodium ion battery using the negative electrode material provided by the present disclosure can meet a variety of application scenarios such as low-speed electric vehicles, home backup power supplies, smart grid peak-shaving energy storage equipment, distributed energy storage, and communication base stations.

[0054] Other features and advantages of the present disclosure will be described in detail in the following detailed description. BRIEF DESCRIPTION OF THE DRAWINGS

[0055] The accompanying drawings are used to provide a further understanding of the present disclosure and constitute a part of the specification. Together with the following specific embodiments, they are used to explain the present disclosure but do not constitute a limitation of the present disclosure. In the accompanying drawings:

[0056] Figure 1 This is a scanning electron microscope (SEM) image of the negative electrode material obtained in Example 1 of the present disclosure;

[0057] Figure 2 This is a comparison chart of the first coulombic efficiency of the battery in Test Example 1 (using the negative electrode material obtained in Example 1) and Test Example 2 of the present disclosure;

[0058] Figure 3 This is a comparison chart of the first coulombic efficiency of the battery in Test Example 1 (using the negative electrode material obtained in Example 4) and Test Example 3 (using the negative electrode material obtained in Example 4) of the present disclosure;

[0059] Figure 4 This is a comparison chart of the cycle performance of batteries at different rates in Test Example 1 (using the negative electrode material obtained in Example 1) and Test Example 2 (using the negative electrode material obtained in Example 1) of the present disclosure;

[0060] Figure 5 It is a comparison chart of the cycle performance at different rates of the batteries in Test Example 1 (using the negative electrode material obtained in Example 4) and Test Example 3 (using the negative electrode material obtained in Example 4) of the present disclosure;

[0061] Figure 6 It is a comparison chart of the cycle performance at different rates of the batteries in Test Example 1 (using the negative electrode material obtained in Example 1) and Test Example 1 (using the negative electrode material obtained in Example 4) of the present disclosure. DETAILED DESCRIPTION

[0062] The specific embodiments of the present disclosure are described in detail below. It should be understood that the specific embodiments described herein are only used to illustrate and explain the present disclosure, and are not used to limit the present disclosure.

[0063] According to the present disclosure, the negative electrode materials in the field of sodium ion batteries are currently mainly carbon materials, including porous hard carbon and soft carbon. The hard carbon layer spacing is large, the microstructure is short-range ordered and long-range disordered, and it exhibits a high reversible capacity when used as the negative electrode of the sodium ion battery, but the disadvantages are low first coulombic efficiency, poor rate performance and unsatisfactory cycle stability. The soft carbon microstructure has a high degree of order and is easy to form a graphite structure at high temperature. When used as the negative electrode material of the sodium ion battery, the rate performance and cycle performance are good, and the first coulombic efficiency is high. The disadvantage is that the sodium storage capacity is relatively low. Therefore, the development of more low-cost soft carbon materials is critical to improving the competitiveness of soft carbon in the application of negative electrode materials for sodium ion batteries.

[0064] The first aspect of the present disclosure provides a method for preparing a negative electrode material for a sodium ion battery, comprising the following steps:

[0065] S1, subjecting gasified ash to a first ball milling process to obtain a first product, wherein the gasified ash includes ash produced during the heavy oil gasification process;

[0066] S2, performing a surface deacidification treatment on the first product to obtain a second product;

[0067] S3, subjecting the second product to a second wet ball milling process and a spray drying process to obtain a third product;

[0068] S4, calcining the third product.

[0069] The present disclosure provides a method for preparing a negative electrode material for a sodium ion battery, wherein the negative electrode material for the sodium ion battery has low cost, readily available raw materials, high initial coulombic efficiency, and good cycle performance, and can have a high sodium storage capacity when used as a negative electrode material for a sodium ion battery. In addition, the negative electrode material is derived from gasification ash, which can expand the high value-added utilization of gasification ash, and the utilization process is more green and environmentally friendly compared to direct incineration of gasification ash.

[0070] In a preferred embodiment, the gasified ash is prepared by removing metal from the ash raw material. Using the gasified ash after metal removal is conducive to avoiding the influence of impurity metals on the performance of the conductive agent and reducing the performance of the negative electrode plate.

[0071] In a specific embodiment, the ash raw material is selected from one or more of vacuum residue gasification ash, residue hydrocracking tail oil gasification ash, deoiled asphalt gasification ash, catalytic oil slurry ash and ethylene tar ash; preferably, deoiled asphalt or catalytic oil slurry gasification ash is used as the raw material for preparing the negative electrode material;

[0072] Optionally, based on the total weight of the ash raw material, the C content in the ash raw material is 82-92 weight%, the H content is 1-10 weight%, the S content is 0.1-5 weight%, the N content is 0.1-5 weight%, the O content is 0.1-5 weight%, and the total content of impurity metals is 0.1-5 weight%, and the impurity metals include Ni, Mo, V, Fe, Na and Ga;

[0073] Preferably, based on the total weight of the gasified ash obtained after metal removal treatment, the C content in the gasified ash obtained after metal removal treatment is 84-92 weight%, the H content is 1-6 weight%, the S content is 0.1-5 weight%, the N content is 0.1-3 weight%, the O content is 0.1-5 weight%, and the total content of impurity metals is 0.1-3 weight%.

[0074] In a specific embodiment, the metal removal process is a hydrometallurgical metal recovery process; optionally, the conditions of the hydrometallurgical metal recovery process include:

[0075] The ash raw material is dried and dehydrated, and then crushed to a particle size of 10 to 100 μm to obtain a crushed ash raw material; the crushed ash raw material is mixed with an acid solution, and then acid hydrolyzed under stirring and reflux; the product obtained by the acid hydrolysis is filtered to obtain gasified ash from which metals have been removed;

[0076] Optionally, the acid solution is selected from one or more of hydrochloric acid, sulfuric acid and nitric acid, preferably sulfuric acid and / or hydrochloric acid; the mixing weight ratio of the acid solution to the crushed ash raw material is 1 to 20:1, preferably 2 to 10:1; optionally, the stirring reflux temperature is room temperature or 45 to 100°C, and the acidolysis treatment time is 3 to 6 hours.

[0077] In one embodiment, the first ball milling treatment condition includes dry ball milling treatment and / or first wet ball milling treatment; preferably, the first wet ball milling treatment. In the present disclosure, during the ball milling treatment, the ball milling jar and the ball milling beads are made of zirconium oxide.

[0078] In a specific embodiment, the conditions of the first wet ball milling treatment include: a ball milling speed of 200 to 1000 rpm, preferably 300 to 800 rpm; a ball milling time of 0.5 to 12 h, preferably 2 to 6 h; a ball milling temperature of 10 to 50° C., preferably 20 to 40° C.; a ball-to-material ratio of 1 to 40, preferably 10 to 30; relative to 1 g of the gasified ash, the amount of the first ball milling solvent is 10 to 200 mL, preferably 20 to 100 mL; optionally, the first ball milling solvent is selected from one or more of ethanol, nitrogen methyl pyrrolidone, cyclohexane, cyclopentane sulfone and tetrahydrofuran.

[0079] In a specific embodiment, the conditions for the dry ball milling treatment include: a ball milling speed of 200 to 450 rpm, preferably 250 to 350 rpm; a ball milling time of 1 to 8 hours, preferably 2 to 6 hours; a ball milling temperature of 10 to 50° C., preferably 20 to 40° C.; and a ball-to-material ratio of 1 to 40, preferably 10 to 30.

[0080] In the present disclosure, when the gasification ash is ball-milled by the first wet ball-milling treatment to obtain the first ball-milling treatment product in the form of a suspension, the suspension needs to be treated to remove the liquid phase, for example, by rotary evaporation to remove moisture. The rotary evaporation drying temperature can be set to 40 to 200°C, preferably 40 to 120°C, and the rotary evaporation time can be 0.1 to 6 hours, preferably 0.5 to 2 hours.

[0081] In the present disclosure, by subjecting the gasification ash to a first ball milling treatment, the gasification ash can be broken into small particles, thereby increasing the conductive sites of the ash and exposing more acid sites to facilitate subsequent cleaning.

[0082] In one embodiment, in step S2, the surface acid removal treatment is water washing treatment or alkali washing treatment; the water washing treatment and alkali washing treatment are independently carried out by stirring cleaning or ultrasonic cleaning.

[0083] In a preferred embodiment, the conditions for the water washing treatment include: contacting the first product with deionized water, and then stirring and filtering to obtain a filter residue; repeating this process more than three times to obtain a second product; optionally, the weight ratio of deionized water to the first product is 1 to 50:1, preferably 10 to 20:1; the conditions for the stirring treatment include: a stirring speed of 100 to 1000 rpm, a stirring time of 2 to 12 hours, preferably, a stirring speed of 200 to 400 rpm, and a stirring time of 4 to 8 hours.

[0084] In a specific embodiment, the conditions for the alkali washing treatment include: the concentration of the alkali solution is 0.1 to 10 mol / L, preferably 0.1 to 5 mol / L; preferably, the alkali solution is selected from an aqueous solution of an alkali; the alkali is selected from one or more of sodium hydroxide, potassium hydroxide, sodium bicarbonate and sodium carbonate; relative to 1 g of the first product, the amount of the alkali solution is 1 to 100 mL, preferably 10 to 50 mL.

[0085] In a specific embodiment, when stirring cleaning is adopted during water washing or alkali washing, the stirring temperature is 20-60°C, the stirring speed is 200-600rpm, and the stirring time is 1-12h; preferably, the stirring temperature is 20-40°C, the stirring speed is 200-450rpm, and the stirring time is 2-6h; when ultrasonic cleaning is adopted during water washing or alkali washing, closed constant temperature ultrasound, ultrasonic time is 3-8h, ultrasonic power is 600-3000W, and ultrasonic frequency is 20-80KHz; preferably, ultrasonic time is 3-7h, ultrasonic power is 400-1000W, and ultrasonic frequency is 40-60KHz.

[0086] In a specific embodiment, the method further comprises: performing solid-liquid separation on the product obtained by the surface acid removal treatment to obtain a solid product; performing freeze-drying on the solid product to obtain the second product;

[0087] Optionally, the freeze-drying treatment conditions include: temperature of -80°C to -20°C, preferably -60°C to -30°C, time of 24 to 96 hours, preferably 48 to 72 hours, vacuum degree of 0.1 to 100 Pa, preferably 1 to 10 Pa.

[0088] In one embodiment, in step S3, the conditions of the second wet ball milling treatment include: a ball milling speed of 200 to 1000 rpm, preferably 600 to 900 rpm; a ball milling time of 1 to 12 h, preferably 6 to 12 h; a ball milling temperature of 10 to 50° C., preferably 20 to 40° C.; a ball-to-material ratio of 1 to 40, preferably 15 to 30; relative to 1 g of the second product, the amount of the second ball milling solvent is 10 to 100 mL, preferably 20 to 100 mL; optionally, the second ball milling solvent is selected from one or more of ethanol, nitrogen methyl pyrrolidone, cyclohexane, cyclopentane sulfone and tetrahydrofuran.

[0089] In one embodiment, in step S3, the conditions of the spray drying process include: a feed temperature of 120 to 200° C., an outlet temperature of 80 to 100° C., a carrier gas flow rate of 12 to 20 L / min, an inlet pressure of 0.3 to 0.8 MPa, and the carrier gas is selected from one or more of nitrogen and argon;

[0090] Preferably, the feed temperature is 140-190° C., the outlet temperature is 90-100° C., the carrier gas flow rate is 14-18 L / min, and the inlet pressure is 0.4-0.6 MPa.

[0091] In one embodiment, during the second wet ball milling process, a coating modifier is also added to coat and modify the gasification ash;

[0092] Preferably, the coating modifier is selected from one or more of phenolic resin, epoxy resin, polyfurfuryl alcohol resin and polyethylene;

[0093] Preferably, the weight ratio of the coating modifier to the second product is 0.02 to 0.2: 1, preferably 0.05 to 0.15: 1. The present invention can form a hard carbon coating on the surface of the obtained negative electrode material by adding the coating modifier during the preparation process, which has the effect of reducing the specific surface area of ​​the gasification ash material and increasing the reversible insertion and extraction of sodium ions.

[0094] In one embodiment, in step S4, the calcination treatment conditions include: heating to 600-1500°C, preferably 750-1200°C, in an inert gas atmosphere, for 1-6h, preferably 2-4h; optionally, the heating rate is 0.5-5°C / min, preferably 1-3°C / min; or,

[0095] The conditions of the calcination treatment include: in an inert gas atmosphere, first heating to 700-1000°C at a first heating rate, keeping warm for 1-6 hours, then heating to 1000-1700°C at a second heating rate, keeping warm for 1-6 hours; preferably, first heating to 800-1000°C at a first heating rate, keeping warm for 2-4 hours, then heating to 1000-1300°C at a second heating rate, keeping warm for 2-4 hours; further preferably, the first heating rate is 1-10°C / min, preferably 1-5°C / min, and the second heating rate is 1-7°C / min, preferably 1-3°C / min;

[0096] Optionally, the inert gas is selected from one or more of nitrogen, helium and argon; the water content of the inert atmosphere is less than 0.1 wt%, and the oxygen content is less than 0.1 wt%.

[0097] A second aspect of the present disclosure provides a negative electrode material for a sodium ion battery prepared according to the method described in the first aspect of the present disclosure.

[0098] In a preferred embodiment, based on the total weight of the negative electrode material, the carbon content is more than 90 weight%, the hydrogen content is less than 3 weight%, and the content of other impurity elements is less than 7 weight%, wherein the other impurity elements include one or more of sulfur, nitrogen, oxygen and impurity metals, and the impurity metals include Ni, Mo, V, Fe, Na and Ga.

[0099] Optionally, the negative electrode material D 50 The particle size is 1-50 μm, the average pore size is 0.1-30 nm, and the BET specific surface area is 1-500 m 2 / g; preferably, the average particle size of the negative electrode material is 5 to 12 μm, the average pore size is 0.5 to 15 nm, and the BET specific surface area is 1 to 200 m 2 / g.

[0100] A third aspect of the present disclosure provides a negative electrode plate for a sodium ion battery, comprising the negative electrode material described in the second aspect of the present disclosure.

[0101] In a specific embodiment, the negative electrode sheet is prepared by a method comprising the following steps: preparing the negative electrode material into a negative electrode slurry, coating the slurry on the surface of a negative electrode current collector, and drying the slurry.

[0102] In a preferred embodiment, the negative electrode slurry comprises the negative electrode material, a conductive material, a dispersant and a binder;

[0103] Preferably, the weight ratio of the negative electrode material: conductive material: dispersant: binder is 60-96: 0.01-5: 1-10: 1-10, preferably 80-96: 0.02-10: 1-5: 1-5.

[0104] In a specific embodiment, the conductive agent is selected from one or more of highly conductive carbon black, conductive graphite, acetylene black, Ketjen black, single-walled carbon nanotubes, multi-walled carbon nanotubes and carbon nanofibers;

[0105] The dispersant is selected from one or more of carboxymethyl cellulose, sodium carboxymethyl cellulose, hydroxyethyl cellulose, sodium alginate, polyvinyl alcohol, chitosan and β-cyclodextrin;

[0106] The binder is selected from one or more of styrene butadiene copolymer, polyacrylic acid, sodium polyacrylate, polyimide, polyvinylidene fluoride, nitrile rubber, butadiene rubber, xanthan gum and gum arabic.

[0107] The conductive material, dispersant and binder in the negative electrode slurry disclosed in the present invention can be purchased through common commercial channels, or prepared by known methods.

[0108] A fourth aspect of the present disclosure provides a sodium ion battery, which includes a positive electrode plate, the negative electrode plate described in the third aspect of the present disclosure, a battery separator and an electrolyte.

[0109] The sodium ion battery using the negative electrode material provided in the present disclosure can meet various application scenarios such as low-speed electric vehicles, home backup power supplies, smart grid peak-shaving energy storage equipment, distributed energy storage, communication base stations, etc.

[0110] In the present disclosure, the positive electrode, electrolyte and separator used in the sodium ion battery can be various materials conventionally adapted in the art, and the present disclosure has no particular limitation on this. For example, the separator can be selected from any one of a polyethylene film, a polypropylene film, a polymer multilayer film modified with an inorganic oxide and a cellulose film, and the positive electrode can be selected from one or more of a metal oxide layered structure, a polyanion structure and a Prussian blue structure. And the composition of the sodium ion battery provided in the present disclosure is a conventional composition in the art.

[0111] In a specific embodiment, the electrolyte is selected from one or more of an ester electrolyte, an ether electrolyte and a sulfone electrolyte;

[0112] Optionally, the ester electrolyte is selected from one or more of ethylene carbonate, vinylene carbonate, vinyl ethylene carbonate, propylene carbonate, ethyl methyl carbonate, dimethyl carbonate, diethyl carbonate and fluorocarbonate;

[0113] Optionally, the ether electrolyte is selected from one or more of 1,3-dioxolane, 1,4-dioxolane, tetrahydrofuran, 2-methyltetrahydrofuran, 1,4-dioxolane, ethylene glycol dimethyl ether, diethylene glycol dimethyl ether, 1H,1H,5H-octafluoropentyl-1,1,2,2-tetrafluoroethyl ether, perfluorohexane, 1,2-bis(cyanoethoxy)ethane and 1,1,2,2-tetrafluoroethyl-2,2,3,3-tetrafluoropropyl ether.

[0114] Optionally, the sulfone electrolyte is selected from one or more of dimethyl sulfoxide, tetramethylene sulfone, cyclopentane, ethyl methyl sulfone, tetramethyl sulfone and methoxyethyl methyl sulfone.

[0115] In a preferred embodiment, the electrolyte is an ether electrolyte.

[0116] The present disclosure is further described in detail below through examples. The raw materials used in the examples can all be obtained through commercial channels.

[0117] The particle size was measured using an optical particle size analyzer, the instrument model being Mastersizer 3000;

[0118] The nitrogen adsorption-desorption curve, average pore size, BET specific surface area and total pore volume test instrument and method are JW-BK200 series, static capacity method measurement;

[0119] The SEM test method is scanning electron microscope, and the instrument model is S4800 of Hitachi, Japan;

[0120] The test method for electrochemical cycle performance is the blue electric test system, and the instrument model is CT3001A.

[0121] Example 1

[0122] (1) The deoiled asphalt ash raw material used in this embodiment (based on the total weight of the asphalt ash raw material, the C content in the ash raw material is 86% by weight, the H content is 4% by weight, the S content is 2% by weight, the N content is 1% by weight, the O content is 5% by weight, and the total content of impurity metals is 2% by weight), and the ash raw material is subjected to hydrometallurgical metal recovery treatment, specifically comprising: drying and dehydrating the asphalt ash raw material and then crushing it to a particle size of 10 to 100 μm; mixing the gasified ash with 1.5 mol / L sulfuric acid in a mass ratio of 10:1, stirring at room temperature, performing acid hydrolysis for 6 hours, filtering after acid hydrolysis to obtain the gasified ash after metal removal, based on the total weight of the gasified ash obtained after metal removal treatment, the C content in the gasified ash obtained after metal removal treatment is 88% by weight, the H content is 4% by weight, the S content is 2.1% by weight, the N content is 1.1% by weight, the O content is 4.5% by weight, and the total content of impurity metals is 0.3% by weight.

[0123] (2) 5 g of the asphalt gasification ash after metal removal was dispersed in 100 mL of ethanol and mixed evenly. The amount of the first ball milling solvent used was 20 mL relative to 1 g of the gasification ash.

[0124] (3) The above mixed material was placed in a 500 mL zirconia ball mill, and 75 g of 1 mm zirconia beads were added, with a ball-to-material ratio of 20. The mixture was placed on a planetary ball mill for the first wet ball milling treatment, with the ball mill speed set at 450 rpm, the time set at 6 h, and the temperature set at 30°C.

[0125] (4) The suspension after ball milling is subjected to rotary evaporation and drying at a temperature set to 60° C. to obtain a first product.

[0126] (5) The dried powder (first product) was collected and placed in a 300 ml beaker. 100 ml of a 0.5 mol / L potassium hydroxide solution was added and mixed evenly. The mixture was then subjected to an alkali washing treatment. The amount of alkali solution used was 20 ml for each gram of the first product.

[0127] (6) The mixed liquid was then stirred using a magnetic stirrer at room temperature (25° C.), a rotation speed of 400 rpm, and a stirring time of 8 h.

[0128] (7) After alkali washing, the material is filtered and then dried by freeze drying. The temperature is set to -60°C, the time is 48 hours, and the vacuum degree is 8Pa.

[0129] (8) The freeze-dried powder (second product) was subjected to a second wet ball milling treatment, and the ball milling conditions were a rotation speed of 600 rpm, a time of 6 h, and a temperature of 30° C. The solvent was 100 mL of ethanol, and the amount of the second ball milling solvent was 20 mL relative to 1 g of the second product, 75 g of 1 mm zirconia beads, and a ball-to-material ratio of 20.

[0130] (9) After the second wet ball milling treatment is completed, the suspension liquid is spray dried. The spray drying conditions are: inlet temperature of 170°C, outlet temperature of 90°C, feed rate of 10ml / min, carrier gas flow rate of 15L / min, inlet pressure of 0.5MPa, and carrier gas is nitrogen gas to obtain a third product.

[0131] (10) The dried powder (third product) was placed in an atmosphere furnace for calcination and carbonization. The calcination conditions were: in an Ar atmosphere, the temperature was raised to 800°C at 3°C / min, then kept at this temperature for 2 hours, and then raised to 1200°C at 2°C / min, and kept at this temperature for 2 hours. Finally, the negative electrode material was obtained.

[0132] Figure 1This is a scanning electron microscope (SEM) image of the negative electrode material prepared in this example. Figure 1 It can be seen that the negative electrode material has a spherical or quasi-spherical structure, and there are pore structures of different sizes on the surface.

[0133] Example 2

[0134] This embodiment refers to the preparation method in Example 1, and the difference from Example 1 is that no ethanol is added in step (2), and the first ball milling treatment in step (3) is directly carried out, that is, dry ball milling treatment is adopted, and the rest of the process is the same as in Example 1, and finally the negative electrode material is obtained.

[0135] Example 3

[0136] This embodiment refers to the preparation method in Example 1, and the difference from Example 1 is that the rotation speed of the second wet ball milling treatment in step (7) is adjusted to 800 rpm, and the rest of the process is the same as Example 1, and finally the negative electrode material is obtained.

[0137] Example 4

[0138] This embodiment refers to the preparation method in Example 1, and the difference from Example 1 is that: during the second wet ball milling treatment in step (7), 0.75 g of phenolic resin is added at the same time as 100 mL of ethanol, and the weight ratio of phenolic resin to the second product is 0.15:1. The rest of the process is the same as in Example 1, and finally a negative electrode material is obtained.

[0139] Example 5

[0140] This example refers to the preparation method in Example 1. The difference between this example and Example 1 is that a one-step calcination method is used in step (9), specifically comprising:

[0141] In an Ar atmosphere, the temperature was raised to 1200° C. at a rate of 3° C. / min and then kept at that temperature for 4 h. The remaining process was the same as in Example 1, and finally the negative electrode material was obtained.

[0142] Example 6

[0143] This embodiment refers to the preparation method of embodiment 1, and the difference from embodiment 1 is that the type of ash raw material and the conditions for metal removal treatment are changed.

[0144] The vacuum residue gasification ash raw material used in this embodiment (based on the total weight of the vacuum residue gasification ash raw material, the C content of the vacuum residue gasification ash raw material is 88% by weight, the H content is 5% by weight, the S content is 2% by weight, the N content is 0.5% by weight, the O content is 3% by weight, and the total content of impurity metals is 1.5% by weight), and the ash raw material is subjected to hydrometallurgical metal recovery treatment. The specific operation is the same as step (1) in Example 1. Based on the total weight of the gasified ash obtained after the metal removal treatment, the C content of the gasified ash obtained after the metal removal treatment is 88.9% by weight, the H content is 5.1% by weight, the S content is 2% by weight, the N content is 0.7% by weight, the O content is 3.2% by weight, and the total content of impurity metals is 0.1% by weight. The remaining processes are also the same as those in Example 1, and finally a negative electrode material is prepared.

[0145] Example 7

[0146] This example refers to the preparation method in Example 1, and the difference from Example 1 is that:

[0147] In step (6), an ultrasonic device is used to perform ultrasonic cleaning on the mixed liquid to perform alkaline cleaning, and the ultrasonic cleaning is performed at a closed constant temperature, the ultrasonic time is 6 hours, the ultrasonic power is 800 W, and the ultrasonic frequency is 40 KHz. The rest of the process is the same as in Example 1, and finally the negative electrode material is obtained.

[0148] Example 8

[0149] (1) This example uses the same asphalt ash raw material as in Example 1, and performs the same hydrometallurgical metal recovery treatment on the ash raw material.

[0150] (2) 5 g of the asphalt gasification ash after metal removal was dispersed in 40 mL of ethanol and mixed evenly. The amount of the first ball milling solvent used was 8 mL relative to 1 g of the gasification ash.

[0151] (3) The above mixed material was placed in a 500 mL zirconia ball mill, and 75 g of 1 mm zirconia beads were added, with a ball-to-material ratio of 15. The mixture was placed on a planetary ball mill for the first wet ball milling treatment, with the ball mill speed set at 150 rpm, the time set at 16 h, and the temperature set at 30°C.

[0152] (4) The suspension after ball milling is subjected to rotary evaporation and drying at a temperature set to 60° C. to obtain a first product.

[0153] (5) Collect the dried powder (first product), put it into a beaker, add 400 ml of 0.5 mol / L potassium hydroxide solution, and the amount of alkali solution is 80 ml relative to 1 g of the first product. Mix well and then perform alkali washing.

[0154] (6) The mixed liquid was then stirred with a magnetic stirrer at room temperature, a rotation speed of 800 rpm, and a stirring time of 8 h to obtain a second product.

[0155] (7) After alkali washing, the material is filtered and then dried by freeze drying. The temperature is set to -60°C, the time is 48 hours, and the vacuum degree is 8Pa.

[0156] (8) After the alkali washing treatment, the powder (second product) was subjected to a second wet ball milling treatment. The ball milling conditions were a rotation speed of 150 rpm, a time of 24 h, and a temperature of 30° C. The solvent was 750 mL of ethanol. With respect to 1 g of the second product, the amount of the second ball milling solvent was 150 mL, 1 mm zirconia beads were 150 g, and the ball-to-material ratio was 30.

[0157] (9) After the second wet ball milling treatment is completed, the suspension liquid is spray dried. The spray drying conditions are: inlet temperature of 160°C, outlet temperature of 90°C, feed rate of 10ml / min, carrier gas flow rate of 15L / min, inlet pressure of 0.5MPa, and carrier gas is nitrogen gas to obtain a third product.

[0158] (10) The dried powder (third product) was placed in an atmosphere furnace for calcination and carbonization. The calcination conditions were: in an Ar atmosphere, the temperature was raised to 600°C at 5°C / min, then kept at this temperature for 2 hours, and then raised to 1500°C at 3°C / min, and kept at this temperature for 2 hours. Finally, the negative electrode material was obtained.

[0159] Example 9

[0160] This example refers to the preparation method in Example 1, and the difference from Example 1 is that the process conditions are changed, specifically including:

[0161] (1) This example uses the same asphalt ash raw material as in Example 1, and performs the same hydrometallurgical metal recovery treatment on the ash raw material.

[0162] (2) 5 g of the asphalt gasification ash after metal removal was dispersed in 80 mL of ethanol and mixed evenly. The amount of the first ball milling solvent used was 16 mL relative to 1 g of the gasification ash.

[0163] (3) The above mixed material was placed in a 500 mL zirconia ball mill, and 75 g of 1 mm zirconia beads were added, with a ball-to-material ratio of 20. The mixture was placed on a planetary ball mill for the first wet ball milling treatment, with the ball mill speed set at 280 rpm, the time set at 8 h, and the temperature set at 30°C.

[0164] (4) The suspension after ball milling is subjected to rotary evaporation and drying at a temperature set to 60° C. to obtain a first product.

[0165] (5) The dried powder (first product) was collected and placed in a beaker. 300 ml of a 0.5 mol / L potassium hydroxide solution was added and mixed evenly. The mixture was then subjected to an alkali washing treatment. The amount of the alkali solution used was 60 ml for each gram of the first product.

[0166] (6) The mixed liquid was then stirred using a magnetic stirrer at room temperature, a rotation speed of 500 rpm, and a stirring time of 10 h.

[0167] (7) After alkali washing, the material is filtered and then dried by freeze drying. The temperature is set to -60°C, the time is 48 hours, and the vacuum degree is 8Pa.

[0168] (8) The freeze-dried powder (second product) was subjected to a second wet ball milling treatment, and the ball milling conditions were a rotation speed of 500 rpm, a time of 5 h, and a temperature of 30° C. The solvent was 500 mL of ethanol, and the amount of the second ball milling solvent was 100 mL relative to 1 g of the second product, 60 g of 1 mm zirconia beads, and the ball-to-material ratio was 12.

[0169] (9) After the second wet ball milling treatment is completed, the suspension liquid is spray dried. The spray drying conditions are: inlet temperature of 160°C, outlet temperature of 90°C, feed rate of 10ml / min, carrier gas flow rate of 15L / min, inlet pressure of 0.5MPa, and carrier gas is nitrogen gas to obtain a third product.

[0170] (10) The dried powder (third product) was placed in an atmosphere furnace for calcination and carbonization. The calcination conditions were: in an Ar atmosphere, the temperature was raised to 750°C at 5°C / min, then kept at this temperature for 2 hours, and then raised to 1400°C at 3°C / min, and kept at this temperature for 2 hours. Finally, the negative electrode material was obtained.

[0171] Comparative Example 1

[0172] This comparative example refers to the preparation method in Example 1, and the difference from Example 1 is that no alkaline washing or water washing treatment is performed (ie, no surface deacidification treatment is performed), and the remaining processes are the same as in Example 1, and finally a negative electrode material is obtained.

[0173] Comparative Example 2

[0174] This comparative example refers to the preparation method in Example 1, and the difference from Example 1 is that no calcination treatment is performed, and the remaining processes are the same as Example 1, and finally a negative electrode material is obtained.

[0175] Comparative Example 3

[0176] This comparative example refers to the preparation method in Example 1, and the difference from Example 1 is that the second wet ball milling treatment and spray drying treatment are not performed, and the remaining processes are the same as Example 1, and finally a negative electrode material is obtained.

[0177] Comparative Example 4

[0178] This comparative example refers to the preparation method in Example 1, and the difference from Example 1 is that the asphalt gasification ash is replaced by coal tar pitch gasification ash, and the rest of the process is the same as Example 1, and finally the negative electrode material is obtained.

[0179] The components and structural parameters of the negative electrode materials prepared in the above examples and comparative examples are listed in the following Table 1.

[0180] Table 1

[0181]

[0182] Test Example 1

[0183] This test example is used to illustrate the electrochemical performance of the products obtained in the examples and comparative examples when used as negative electrode materials for sodium ion batteries.

[0184] The products obtained in the examples and comparative examples were used as negative electrodes to assemble sodium ion batteries, and their electrochemical performance was tested. The specific steps are as follows:

[0185] (1) The products (negative electrode materials) obtained in the above-mentioned embodiments and comparative examples were mixed with Super-P (conductive carbon black material), CMC (carboxymethyl cellulose, dispersant) and SBR (styrene-butadiene rubber, binder) in a mass ratio of 92:3:2:3 (1:0.0326:0.0217:0.0326) in a vacuum homogenizer for 4 hours, and then coated on a copper current collector and dried in a vacuum oven at 120°C for 8 hours to obtain a negative electrode sheet.

[0186] (2) The prepared negative electrode sheet was used as the negative electrode of the battery, the metal sodium sheet was used as the positive electrode, glass fiber was selected as the separator, and 1 mol / L NaPF6 (the solvent was diethylene glycol dimethyl ether, DEGDME) was used as the electrolyte to assemble a button half-cell in a glove box.

[0187] Test Example 2

[0188] The negative electrode material prepared in Example 1 was used to assemble a battery according to the method in Test Example 1. The difference from Test Example 1 was that the ether electrolyte was replaced with an ester electrolyte (1 mol / L NaPF6 in DEC:EC=1:1Vol%), and the rest of the process was the same as Test Example 1.

[0189] Test Example 3

[0190] The negative electrode material prepared in Example 4 was used to assemble a battery according to the method in Test Example 1. The difference from Test Example 1 was that the ether electrolyte was replaced with an ester electrolyte (1 mol / L NaPF6 in DEC:EC=1:1Vol%), and the rest of the process was the same as Test Example 1.

[0191] The batteries obtained in the above test examples 1 to 3 were subjected to charge and discharge tests using a BlueDian system. The parameters were set as follows: the current density was 0.1C for the first cycle, and the subsequent rate was changed (0.2C, 0.5C, and 1.0C, respectively), and the voltage range was 0.001 to 3.0V. The test results are listed in Table 2 below.

[0192] Table 2

[0193]

[0194]

[0195] By comparing the data of Test Example 1 and Test Example 2 of the negative electrode material of the sodium ion battery, it can be found that the first coulombic efficiency in the ester electrolyte is low, only 23.5%, while the use of the ether electrolyte can reach a first coulombic efficiency of 88.1%.

[0196] By comparing the battery data of the negative electrode materials prepared by Example 1 and Example 4 in Test Example 1, it can be found that the negative electrode material modified by coating the gasified ash with phenolic resin has basically no effect on the capacity; further, by Figure 4 and Figure 5 It can be seen that the rate performance of the negative electrode material provided in the present application in ether electrolyte is significantly better than that in ester electrolyte; combined with Figure 6 After high-rate charge and discharge, the battery specific capacity of the two negative electrode materials prepared in Example 1 and Example 4 increased, showing a higher sodium storage capacity.

[0197] It can be seen from the performance of the negative electrode materials in Test Examples 2 and 3 that after the gasification ash is coated and modified with phenolic resin, the first coulombic efficiency is increased from 23.5% in Test Example 2 (the negative electrode material is not coated and modified with phenolic resin) to 43.6% in Test Example 3 (the negative electrode material is coated and modified with phenolic resin).

[0198] By comparing the data of the negative electrode materials provided in Example 1 and Comparative Example 1 in Test Example 1, it can be seen that the lack of treatment of gasified ash in Comparative Example 1 will reduce the performance of the prepared negative electrode material as a negative electrode material for a sodium ion battery. Among them, if alkali washing or water washing is not performed to remove the residual acid on the surface of the gasified ash after metal removal, the obtained negative electrode material has almost no capacity (the first charge specific capacity and the first discharge specific capacity are low), which shows that the sodium ion battery negative electrode material prepared by the method provided in the present disclosure using the gasified ash after metal removal as a raw material in the embodiment shows a higher first coulomb efficiency and specific capacity in an ether electrolyte.

[0199] By comparing Example 1 with Example 9, it can be seen that in Example 1, the optimized process conditions provided by the present disclosure are used to prepare the negative electrode material. Compared with Example 9, the sodium ion battery in Test Example 1 using the negative electrode material prepared in Example 1 shows higher first coulombic efficiency and specific capacity.

[0200] Example 8 was compared with Example 9. Example 9 prepared the negative electrode material according to the condition range provided in the present disclosure. Compared with Example 8, the sodium ion battery using the negative electrode material prepared in Example 9 in Test Example 1 showed higher first coulombic efficiency and specific capacity.

[0201] By comparing Example 1 with Example 5, it can be seen that Example 1 adopts a two-stage calcination process, and Example 5 adopts a one-stage calcination process. Compared with Example 5, the sodium ion battery using the negative electrode material prepared in Example 1 in Test Example 1 shows higher first coulombic efficiency and specific capacity.

[0202] The preferred embodiments of the present disclosure are described in detail above; however, the present disclosure is not limited to the specific details in the above embodiments. Within the technical concept of the present disclosure, a variety of simple modifications can be made to the technical solution of the present disclosure, and these simple modifications all fall within the protection scope of the present disclosure.

[0203] It should also be noted that the various specific technical features described in the above specific embodiments can be combined in any suitable manner without contradiction. In order to avoid unnecessary repetition, the present disclosure will not further describe various possible combinations.

[0204] In addition, various embodiments of the present disclosure may be arbitrarily combined, and as long as they do not violate the concept of the present disclosure, they should also be regarded as the contents disclosed by the present disclosure.

Claims

1. A method for preparing a negative electrode material for a sodium ion battery, characterized in that: The following steps are involved: S1, subjecting gasified ash to a first ball milling process to obtain a first product, wherein the gasified ash includes ash produced in a heavy oil gasification process; S2, performing a surface deacidification treatment on the first product to obtain a second product; S3, subjecting the second product to a second wet ball milling process and a spray drying process to obtain a third product; S4, calcining the third product.

2. The method according to claim 1, characterized in that The gasified ash is prepared by removing metal from the ash raw material; Preferably, the metal removal process is a hydrometallurgical metal recovery process; optionally, the conditions of the hydrometallurgical metal recovery process include: The ash raw material is dried and dehydrated, and then crushed to a particle size of 10 to 100 μm to obtain a crushed ash raw material; the crushed ash raw material is mixed with an acid solution, and then acid hydrolyzed under stirring and reflux; the product obtained by the acid hydrolysis is filtered to obtain gasified ash from which metals have been removed; Optionally, the acid solution is selected from one or more of hydrochloric acid, sulfuric acid and nitric acid, preferably sulfuric acid and / or hydrochloric acid; the mixing weight ratio of the acid solution to the crushed ash raw material is 1 to 20:1, preferably 2 to 10:1; Optionally, the stirring reflux temperature is room temperature or 45 to 100°C, and the acid hydrolysis treatment time is 3 to 6 hours; Optionally, the ash raw material is selected from one or more of vacuum residue gasification ash, residue hydrocracking tail oil gasification ash, deoiled asphalt gasification ash, catalytic oil slurry ash and ethylene tar ash; Optionally, based on the total weight of the ash raw material, the C content in the ash raw material is 82-92 weight%, the H content is 1-10 weight%, the S content is 0.1-5 weight%, the N content is 0.1-5 weight%, the O content is 0.1-5 weight%, and the total content of impurity metals is 0.1-5 weight%, and the impurity metals include Ni, Mo, V, Fe, Na and Ga; Preferably, based on the total weight of the gasified ash obtained after metal removal treatment, the C content in the gasified ash obtained after metal removal treatment is 84-92 weight%, the H content is 1-6 weight%, the S content is 0.1-5 weight%, the N content is 0.1-3 weight%, the O content is 0.1-5 weight%, and the total content of impurity metals is 0.1-3 weight%.

3. The method according to claim 1, characterized in that: The conditions of the first ball milling treatment include dry ball milling treatment and / or first wet ball milling treatment; preferably, the first wet ball milling treatment; Optionally, the conditions of the first wet ball milling treatment include: a ball milling speed of 200 to 1000 rpm, preferably 300 to 800 rpm; a ball milling time of 0.5 to 12 h, preferably 2 to 6 h; a ball milling temperature of 10 to 50° C., preferably 20 to 40° C.; a ball-to-material ratio of 1 to 40, preferably 10 to 30; relative to 1 g of the gasified ash, the amount of the first ball milling solvent is 10 to 200 mL, preferably 20 to 100 mL; optionally, the first ball milling solvent is selected from one or more of ethanol, nitrogen methyl pyrrolidone, cyclohexane, cyclopentane sulfone and tetrahydrofuran; Preferably, the method further comprises: drying the product obtained by wet ball milling by rotary evaporation; preferably, the conditions of the rotary evaporation include: a temperature of 40 to 200° C., preferably 40 to 120° C.; Optionally, the conditions for the dry ball milling treatment include: a ball milling speed of 200 to 450 rpm, preferably 250 to 350 rpm; a ball milling time of 1 to 8 hours, preferably 2 to 6 hours; a ball milling temperature of 10 to 50° C., preferably 20 to 40° C.; and a ball-to-material ratio of 1 to 40, preferably 10 to 30.

4. The method according to claim 1, characterized in that: In step S2, the surface acid removal treatment is water washing treatment or alkali washing treatment; the water washing treatment and alkali washing treatment are independently carried out by stirring washing or ultrasonic washing; Optionally, the conditions of the water washing treatment include: contacting the first product with deionized water, and then stirring and filtering to obtain a filter residue; repeating the process for more than 3 times to obtain a second product; Optionally, the weight ratio of deionized water to the first product is 1 to 50:1, preferably 10 to 20:1; the conditions of the stirring treatment include: a stirring speed of 100 to 1000 rpm, a stirring time of 2 to 12 h, preferably, a stirring speed of 200 to 400 rpm, and a stirring time of 4 to 8 h; Optionally, the conditions of the alkali washing treatment include: the concentration of the alkali solution is 0.1 to 10 mol / L, preferably 0.1 to 5 mol / L; preferably, the alkali solution is selected from an aqueous solution of an alkali; the alkali is selected from one or more of sodium hydroxide, potassium hydroxide, sodium bicarbonate and sodium carbonate; relative to 1 g of the first product, the amount of the alkali solution is 1 to 100 mL, preferably 10 to 50 mL; Optionally, when stirring cleaning is adopted, the stirring temperature is 20-60°C, the stirring speed is 200-600rpm, and the stirring time is 1-12h; preferably, the stirring temperature is 20-40°C, the stirring speed is 200-450rpm, and the stirring time is 2-8h; Optionally, when ultrasonic cleaning is adopted, the ultrasound is carried out in a closed constant temperature environment, the ultrasound time is 3 to 8 hours, the ultrasound power is 600 to 3000 W, and the ultrasound frequency is 20 to 80 KHz; preferably, the ultrasound time is 3 to 7 hours, the ultrasound power is 400 to 1000 W, and the ultrasound frequency is 40 to 60 KHz.

5. The method according to claim 1, characterized in that In step S3, the conditions of the second wet ball milling process include: The ball milling speed is 200-1000 rpm, preferably 600-900 rpm; the ball milling time is 1-12 h, preferably 6-12 h; the ball milling temperature is 10-50° C., preferably 20-40° C.; the ball-to-material ratio is 1-40, preferably 15-30; relative to 1 g of the second product, the amount of the second ball milling solvent is 10-100 mL, preferably 20-100 mL; optionally, the second ball milling solvent is selected from one or more of ethanol, nitrogen methyl pyrrolidone, cyclohexane, cyclopentane and tetrahydrofuran; Preferably, in step S3, the conditions of the spray drying treatment include: a feed temperature of 120 to 200°C, an outlet temperature of 80 to 100°C, a carrier gas flow rate of 12 to 20 L / min, an inlet pressure of 0.3 to 0.8 MPa, and the carrier gas is selected from one or more of nitrogen and argon; Preferably, the feed temperature is 140-190° C., the outlet temperature is 90-100° C., the carrier gas flow rate is 14-18 L / min, and the inlet pressure is 0.4-0.6 MPa.

6. The method according to claim 1, characterized in that During the second wet ball milling process, a coating modifier is added to coat and modify the gasification ash; Preferably, the coating modifier is selected from one or more of phenolic resin, epoxy resin, polyfurfuryl alcohol resin and polyethylene; Preferably, the weight ratio of the coating modifier to the second product is 0.02 to 0.2:1, preferably 0.05 to 0.15:

1.

7. The method according to claim 1, characterized in that In step S4, the calcination treatment conditions include: heating to 600-1500°C, preferably 750-1300°C, in an inert gas atmosphere, and keeping the temperature for 1-6h, preferably 2-4h; optionally, the heating rate is 0.5-5°C / min, preferably 1-3°C / min; or, The conditions of the calcination treatment include: in an inert gas atmosphere, first heating to 700-1000°C at a first heating rate, keeping warm for 1-6 hours, then heating to 1000-1700°C at a second heating rate, keeping warm for 1-6 hours; preferably, first heating to 800-1000°C at a first heating rate, keeping warm for 2-4 hours, then heating to 1000-1300°C at a second heating rate, keeping warm for 2-4 hours; further preferably, the first heating rate is 1-10°C / min, preferably 1-5°C / min, and the second heating rate is 1-7°C / min, preferably 1-3°C / min; Optionally, the inert gas is selected from one or more of nitrogen, helium and argon; the water content of the inert gas is less than 0.1 wt%, and the oxygen content is less than 0.1 wt%.

8. A negative electrode material for a sodium ion battery prepared according to the method of any one of claims 1 to 7.

9. The negative electrode material according to claim 8, characterized in that Based on the total weight of the negative electrode material, the carbon content is 90 weight % or more, the hydrogen content is 3 weight % or less, and the content of other impurity elements is 7 weight % or less, wherein the other impurity elements include one or more of sulfur, nitrogen, oxygen and impurity metals, and the impurity metals include Ni, Mo, V, Fe, Na and Ga; Optionally, the negative electrode material D 50 The particle size is 1-50 μm, and the BET specific surface area is 1-500 m 2 / g; preferably, the average particle size of the negative electrode material is 5 to 12 μm, and the BET specific surface area is 1 to 200 m 2 / g.

10. A negative electrode plate for a sodium ion battery, characterized in that: Contains the negative electrode material as described in claim 8 or 9.

11. The negative electrode sheet according to claim 10, characterized in that: The negative electrode sheet is prepared by a method comprising the following steps: preparing the negative electrode material into a negative electrode slurry, coating the negative electrode slurry on the surface of the negative electrode current collector, and drying the slurry; Preferably, the negative electrode slurry comprises the negative electrode material, a conductive material, a dispersant and a binder; Preferably, the weight ratio of the negative electrode material: conductive material: dispersant: binder is 60 to 96: 0.01~5:1~10:1~10, preferably 80~96: 0.02~10:1~5:1~5; Optionally, the conductive agent material is selected from one or more of highly conductive carbon black, conductive graphite, acetylene black, Ketjen black, single-walled carbon nanotubes, multi-walled carbon nanotubes and carbon nanofibers; Optionally, the dispersant is selected from one or more of carboxymethyl cellulose, sodium carboxymethyl cellulose, hydroxyethyl cellulose, sodium alginate, polyvinyl alcohol, chitosan and β-cyclodextrin; Optionally, the binder is selected from one or more of styrene butadiene copolymer, polyacrylic acid, sodium polyacrylate, polyimide, polyvinylidene fluoride, nitrile rubber, butadiene rubber, xanthan gum and gum arabic.

12. A sodium ion battery, characterized in that: The sodium ion battery comprises a positive electrode plate, the negative electrode plate described in claim 10 or 11, a battery separator and an electrolyte.

13. The sodium ion battery according to claim 12, characterized in that: The electrolyte is selected from one or more of an ester electrolyte, an ether electrolyte and a sulfone electrolyte; Optionally, the ester electrolyte is selected from one or more of ethylene carbonate, vinylene carbonate, vinyl ethylene carbonate, propylene carbonate, ethyl methyl carbonate, dimethyl carbonate, diethyl carbonate and fluorocarbonate; Optionally, the ether electrolyte is selected from one or more of 1,3-dioxolane, 1,4-dioxolane, tetrahydrofuran, 2-methyltetrahydrofuran, 1,4-dioxolane, ethylene glycol dimethyl ether, diethylene glycol dimethyl ether, 1H,1H,5H-octafluoropentyl-1,1,2,2-tetrafluoroethyl ether, perfluorohexane, 1,2-bis(cyanoethoxy)ethane and 1,1,2,2-tetrafluoroethyl-2,2,3,3-tetrafluoropropyl ether; Optionally, the sulfone electrolyte is selected from one or more of dimethyl sulfoxide, tetramethylene sulfone, ethyl methyl sulfone, tetramethyl sulfone, cyclopentane and methoxyethyl methyl sulfone.

Citation Information

Patent Citations

  • Performance improvement method of coal-based sodium ion battery negative electrode material and application thereof

    CN111293309A

  • Performance improvement method and application of sodium-ion battery carbon-based negative electrode material

    CN113526489A

  • Preparation method of soft and hard carbon composite nanomaterial

    CN114516627A

  • Method for preparing electrode material from coal-to-oil residue

    CN106410202A

  • Method for treating petroleum coke gasification ash

    CN112520749A